Development and validation of job satisfaction instrument for offshore catering employees in Malaysia - Abdul Majid, Mohd Aliff (2019)
Job satisfaction is essential in offshore catering. Understanding their satisfaction can be a valuable approach to enhance organizational performance. However, the employees view offshore catering job as a stepping stone rather than a long-life career path and retaining the employees become challenging. Studies on job satisfaction have been conducted but less is known about job satisfaction among these employees and its relationship towards intention to leave and industry commitment. The purpose of this study was to develop a job satisfaction instrument based on the experiences of offshore catering employees in Malaysia. The instrument was named as ‘Satisfaction with Offshore Job Instrument’ (SwOJI). An exploratory sequential mixed methods design was employed, corresponding to DeVellis’ (2012) scale development guidelines. The results of qualitative phase by analyzing interviews of 13 participants (n=13) using thematic analysis revealed 70 codes. A preliminary instrument based on the qualitative findings was constructed and after consulting the content experts, the SwOJI consisted of 71 items. The instrument was administered to offshore catering employees in Malaysia and 309 usable questionnaires (n=309) were collected and analyzed. The psychometric properties of SwOJI were examined using exploratory factor analysis (EFA) and confirmatory factor analysis (CFA). The EFA revealed an eight-factor solution and the final model fit of the measurement model (χ2/df=2.22, CFI=.90, IFI=.90, TLI=.88, RMSEA=.06) was found to be acceptable, confirming the convergent and discriminant validity. In relation to criterion-related validity, it was found that job satisfaction had a moderate, negative relationship to intention to leave (r=-.33) and had a strong, positive relationship (r=.69) with industry commitment, indicating both hypotheses were supported. Significantly, this study produced a bespoke instrument to accurately measure the job satisfaction among offshore catering employees. The current study provides fresh insight in the context of employees working in offshore catering and concludes a better nomological understanding of the relationship between job satisfaction, intention to leave and industry commitment. In addition, the study extends the existing body of knowledge within the human resource and organizational research. The practitioner may use the findings to formulate strategies to manage and effectively improve offshore catering employees’ job satisfaction that will enhance their commitment to the industry and reduce their intention to leave the job.